CHARACTERISING FAT DISTRIBUTION AND RESPONSE TO WEIGHT LOSS IN IIH. Issue 12 (15th November 2016) - Hornby, Catherine; Botfield, Hannah; O'Reilly, Michael; Markey, Keira; Scotton, William; Tomlinson, Jeremy; Arlt, Wiebke; Sinclair, Alexandra
Abstract : Idiopathic intracranial hypertension (IIH) is a condition characterised by raised intracranial pressure of unknown pathogenesis. Over 94% of sufferers are young, obese women, but little is known about their metabolic phenotype. Previous studies measuring waist-hip ratios in IIH have suggested predominant lower body adiposity. We aimed to characterise the pattern of fat distribution using dual energy X-ray absorptiometry (DEXA) and metabolic phenotype (fasting lipids, glucose and insulin) and evaluate changes following weight loss. At baseline, IIH (n=29) had a similar centripetal fat distribution and lipid profile to BMI and gender matched obese controls (n=47). The glucose:insulin ratio (G:I) and HOMA-IR were elevated at baseline indicating insulin resistance in IIH, although akin to what was seen in simple obesity (G:I 0.4±0.2 vs 0.8±0.9 and HOMA-IR 2.1±2.1 vs 1.6±1.1). Weight loss resulted in a significant reduction in disease activity (ICP and papilloedema) alongside a significant reduction in fat mass (−4.1±2.7%, p<0.001), predominantly from the truncal region (−4.7±3.7%) compared to the limbs (1.1±2.1%, p<0.001). These results indicate that fat distribution in IIH is centripetal, similar to simple obesity. Clinical resolution of IIH is associated with preferential loss of truncal fat. The role of truncal adiposity in the pathogenesis of IIH warrants further investigation.